Evaluation of the efficacy and safety of orally administered BI425809 during a 12‐week treatment period compared with placebo in patients with cognitive impairment due to Alzheimer's disease: Human: Putative therapeutic results for Alzheimer's and related dementias. (7th December 2020) - Wunderlich, Glen; Blahova, Zuzana; Garcia, Miguel; Huang, Songqiao; Pollentier, Stephane; Jessen, Frank
Abstract: Background: Although currently approved therapies for Alzheimer's dementia (AD) are used to treat impairments in memory and function, there is an unmet need for additional symptomatic therapies in mild‐to‐moderate AD. As N‐methyl‐D‐aspartate (NMDA) receptor hypofunction has been hypothesised to be associated with cognitive impairment in AD, improving post‐synaptic NMDA receptor signalling through glycine transporter 1 (GlyT1) inhibition may improve cognitive function. This proof of clinical concept study investigated the efficacy and safety of the investigational drug BI 425809, a GlyT1 inhibitor, in mild‐to‐moderate AD and evaluated dose‐ranging data to define a suitable dose of BI 425809 in this population. Method: A Phase II, multicentre, double‐blind, parallel‐group study including patients aged ≥55 years with mild‐to‐moderate AD (according to the recommendations from the National Institute on Aging‐Alzheimer's Association workgroups on diagnostic guidelines for AD), a mini‐mental state exam score of 15–26 at screening, and a reliable study partner who was in close contact with the patient and could contribute to the neuropsychological rating scales. Concomitant acetylcholinesterase inhibitor use was permitted but not required. Eligible patients were randomised (1:1:1:1:1) to receive BI 425809 2, 5, 10, 25 mg, or placebo once daily for 12 weeks. The primary endpoint was change from baseline in Alzheimer's Disease Assessment Scale‐cognitive subscale (ADAS‐Cog11 ) total score at Week 12. Secondary endpoints included change from baseline in the Alzheimer's Disease Cooperative Study/Activities of Daily Living score and Clinician's Interview‐Based Impression of Change at Week 12. The pre‐specified primary analyses for proof of concept and dose finding was the multiple comparison procedure with modelling for mixed model repeated measures. Adverse events were evaluated throughout the study. Result: A total of 610 patients were randomised. No significant non‐flat dose‐response relationship was detected for the primary endpoint. Secondary endpoints similarly did not detect any significant benefit for BI 425809 treatment groups compared with placebo. BI 425809 was generally well tolerated with no new safety issues identified. Conclusion: No clinically meaningful changes from baseline were observed across a range of BI 425809 doses administered to patients with mild‐to‐moderate AD. Funding: Boehringer Ingelheim: Study 1346‐0023 (NCT02788513).